2010
DOI: 10.1021/jf1019592
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of 346 Multiresidue Pesticides in Grapes by PSA-MSPD and GC-MS-SIM

Abstract: The article demonstrates a method of simultaneous determination for 352 pesticide residues in grapes using primary-secondary amine (PSA) matrix solid phase dispersion (MSPD) cleanup and gas chromatography-mass spectrometry-selected ion monitoring (GC-MS-SIM). Grape samples (15 g) were mixed with 6 g of anhydrous magnesium sulfate and 1.5 g of sodium chloride, and then extracted with acetonitrile (15 mL) and cleaned up with 0.3 g of dispersive PSA. The analytes were determined by GC-MS-SIM. Four injections for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The target and qualifier ions (MS) were determined by injection of individual pesticide standards, using full-scan mode (40-650 m/z). The product ions were compared with other methods (Lian et al 2010;Rocha et al 2011;Wong et al 2010;X. Yang et al 2011) and supported by NIST Mass Spectral Search Program (version 2.0, 2005) library to create a selected ion monitoring (SIM; Table 1).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The target and qualifier ions (MS) were determined by injection of individual pesticide standards, using full-scan mode (40-650 m/z). The product ions were compared with other methods (Lian et al 2010;Rocha et al 2011;Wong et al 2010;X. Yang et al 2011) and supported by NIST Mass Spectral Search Program (version 2.0, 2005) library to create a selected ion monitoring (SIM; Table 1).…”
Section: Sample Preparationmentioning
confidence: 99%
“…High throughput screening methods with simple sample preparation were preferable for target pesticides, such as gas chromatography/mass spectrometry (GC/MS) (Lagunas-Allue, Sanz-Asensio, & Martinez-Soria, 2010;Li, Zhang, & Shi, 2011;Lian et al, 2010;Satpathy, Tyagi, & Gupta, 2011) and liquid chromatography/tandem mass spectrometry (LC-MS/MS) methods (Pico & Kozmutza, 2007;Venkateswarlu, Mohan, Kumar, & Seshaiah, 2007). Furthermore, non-target pesticides should also be considered and timeof-flight (TOF) mass spectrometry (Dasgupta et al, 2010) or the normal GC/MS method with scan mode (Satpathy et al, 2011) was reported for this purpose.…”
Section: Introductionmentioning
confidence: 98%
“…At present, this method is mainly used to extract solid, semi‐solid and highly viscous samples . Dispersants used in MSPD are TiO 2 , primary‐secondary amine and so on. However, these dispersants lack selectivity, causing many impurities exist in the eluent.…”
Section: Introductionmentioning
confidence: 99%